The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s11481-015-9618-9
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Neurodegenerative Process Associated to Parkinson’s Disease by CD4+ T-cells

Abstract: Neuroinflammation constitutes a fundamental process involved in the physiopathology of Parkinson's disease (PD). Microglial cells play a central role in the outcome of neuroinflammation and consequent neurodegeneration of dopaminergic neurons in the substantia nigra. Current evidence indicates that CD4+ T-cells infiltrate the central nervous system (CNS) in PD, where they play a critical role determining the functional phenotype of microglia, thus regulating the progression of the neurodegenerative process. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 143 publications
1
50
0
Order By: Relevance
“…The extensive microglial activation, persistent viral infection and inflammation observed in these mice recalls the pathology observed in other persistent CNS infections, such as patients chronically infected with HIV. 64 There is an increasing body of work indicating that chronically activated microglia, regulated by CD4+ T cells, can result in neurodegeneration through the chronic secretion of factors such as TNF, NO and IL-1β 65, 66, 67 Given the absence of the apoptosis observed when only CD4+ T cells are present in the CNS, it is likely that the observed neurodegeneration in CD4+ T-cell recipients is the result of gliosis mediated cytotoxicity. The precise molecules and mechanisms involved in this CD4+ T-cell-mediated neurodegeneration are currently under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The extensive microglial activation, persistent viral infection and inflammation observed in these mice recalls the pathology observed in other persistent CNS infections, such as patients chronically infected with HIV. 64 There is an increasing body of work indicating that chronically activated microglia, regulated by CD4+ T cells, can result in neurodegeneration through the chronic secretion of factors such as TNF, NO and IL-1β 65, 66, 67 Given the absence of the apoptosis observed when only CD4+ T cells are present in the CNS, it is likely that the observed neurodegeneration in CD4+ T-cell recipients is the result of gliosis mediated cytotoxicity. The precise molecules and mechanisms involved in this CD4+ T-cell-mediated neurodegeneration are currently under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo and in vitro studies have demonstrated that overexpression of α-syn can induce the MHC-II expression by microglia. The MHC-II expression in microglia cells can play an important role in the immune responses (innate and adaptive) in PD (Michelucci et al, 2009; Harms et al, 2013; Gonzalez et al, 2015). …”
Section: Parkinson and Microgliamentioning
confidence: 99%
“…While the current study is the first to report alterations in both CD4 + and NKT cells in the brain of DLB patients and animals overexpressing α-syn, several groups have described disturbances in various CD4+/CD8 + T cell subsets and NK cells [40,[60][61][62]. For example, one recent study demonstrated that α-syn oligomers and fibrils changed the ratio of CD8 + to CD4 + T cells in the CNS and reduced the expression of STAT3, CD25, and CD127 in CD3 + CD4 + T cells.…”
Section: Discussionmentioning
confidence: 70%